Vernacular Architecture as Self-Determination: Venturi, Scott Brown and the Controversy over Philadelphia's Crosstown Expressway, 1967-1973 - Sebastian Haumann (Footprint)
Between 1967 and 1972 Robert Venturi and Denise Scott Brown worked on two projects simultaneously. One culminated in Learning from Las Vegas, their renowned contribution to architectural theory; the other reflected their political engagement in the so-called Crosstown Controversy. In this project, Venturi and Scott Brown spoke on behalf of a citizens’ initiative opposing a proposed inner-city expressway in the South Street area of Philadelphia. The aesthetic criticism exemplified in their study of Las Vegas found parallels in the political critique embodied by the alternative scheme they developed for the Philadelphia citizen group. This scheme proposed to revalorise the vernacular architecture of the existing neighbourhood, against the wholesale demolition implied in the official plans for the Crosstown Expressway.